Here's the question you clicked on:
NotTim
USe an example to show that (k+m)u=ku+mu
i was thinking: why not just use dummy variables, like k=10, i=9 and m=3, but is there something deeper?
Nope, that is the correct course of action. That would be the only way to prove by example.
i was thinking that it was MUCH more complex than that..
If (k + m)u = ku + mu , you should be able to set variables k,m and u equal to any random numbers and both sides should come out equal.
I doubt if it is any more complex than that.
this was simple. to me, simple means secretly hard. thank you for clarifying